2016
DOI: 10.1111/tra.12450
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary balance: conservation vs innovation in ciliate membrane trafficking

Abstract: As most of eukaryotic diversity lies in single-celled protists, they represent unique opportunities to ask questions about the balance of conservation and innovation in cell biological features. Among free-living protists the ciliates offer ease of culturing, a rich array of experimental approaches, and versatile molecular tools, particularly in Tetrahymena thermophila and Paramecium tetraurelia. These attributes have been exploited by researchers to analyze a wealth of cellular structures in these large and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 143 publications
(254 reference statements)
3
30
0
Order By: Relevance
“…Recent studies of the evolution of genes involved in membrane trafficking have focused on an overview of all eukaryotes with the goals of establishing the origins of membrane-traffic regulating proteins in the last common eukaryotic ancestor and defining the species distribution of various families of traffic-regulating proteins (11,12). These studies have identified common features of proteins that regulate membrane traffic (11) and also revealed that extensive gene duplication has allowed lineage-specific diversification of coat proteins and other membrane traffic regulators, such as the Rab GTPases (13,14). Our earlier study of available annotated genomes in 2005 suggested that the gene duplication giving to rise to the two CHCencoding genes occurred as a result of one of the whole genome duplications contributing to chordate evolution (2).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the evolution of genes involved in membrane trafficking have focused on an overview of all eukaryotes with the goals of establishing the origins of membrane-traffic regulating proteins in the last common eukaryotic ancestor and defining the species distribution of various families of traffic-regulating proteins (11,12). These studies have identified common features of proteins that regulate membrane traffic (11) and also revealed that extensive gene duplication has allowed lineage-specific diversification of coat proteins and other membrane traffic regulators, such as the Rab GTPases (13,14). Our earlier study of available annotated genomes in 2005 suggested that the gene duplication giving to rise to the two CHCencoding genes occurred as a result of one of the whole genome duplications contributing to chordate evolution (2).…”
Section: Introductionmentioning
confidence: 99%
“…Also trimeric G-proteins, GPCRs, luminal CaBPs in Ca 2+ stores, and annexins have been only tentatively identified in ciliates (Plattner 2010b). Other proteins identified insufficiently in ciliates are those involved in nuclear death, an apoptosis-related process involved in elimination of the old macronucleus after conjugation (Guerrier et al 2017). There would be many more examples.…”
Section: Proteins Under Discussionmentioning
confidence: 99%
“…Essentially, the inventory of SNAREs is high already in unicellular ("lower") eukaryotes, not only in ciliates (Plattner 2010a,b) but also in myxamoebae and chlorophyceae (Sanderfoot 2007). This abundance not only with SNAREs (including those involved in the secretory pathway) but also with GTPases (Bright et al 2010;Guerrier et al 2017).…”
Section: The Tandem Of Gtpases and Snaresmentioning
confidence: 98%
See 2 more Smart Citations